Erythrocyte fatty acid profiles and plasma homocysteine, folate and vitamin B6 and B12 in recurrent depression: Implications for co-morbidity with cardiovascular disease. Issue 3 (30th October 2015) - Assies, Johanna; Mocking, Roel J.T.; Lok, Anja; Koeter, Maarten W.J.; Bockting, Claudi L.H.; Visser, Ieke; Pouwer, François; Ruhé, Henricus G.; Schene, Aart H.
Abstract: Oxidative stress induced interactions between fatty acid (FA) and one-carbon metabolism may be involved in co-occurrence of major depressive disorder (MDD) and cardiovascular disease (CVD), which have been scarcely studied together. In 137 recurrent MDD-patients vs. 73 age- and sex-matched healthy controls, we simultaneously measured key components of one-carbon metabolism in plasma (homocysteine, folate, vitamins B6 and B12 ), and of FA-metabolism in red blood cell membranes [main polyunsaturated fatty acids (PUFAs) eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and arachidonic acid (AA) and structural FA-indices (chain length, unsaturation, peroxidation)]. Results show significant positive associations of folate with EPA, DHA, and the peroxidation index, which were similar in patients and controls. After correction for confounders, these associations were lost except for EPA. Associations between B-vitamins and FA-parameters were non-significant, but also similar in patients and controls. Homocysteine and DHA were significantly less negatively associated in patients than in controls. In conclusion, these data indicate similarities but also differences in associations between parameters of one-carbon and FA-metabolism in recurrent MDD patients vs. controls, which may reflect differences in handling of oxidative stress. Further research should test the consequences of these differences, particularly the premature development of CVD in MDD. Highlights: Oxidative stress influences relations between one-carbon and fatty acid metabolism. These relations have only scarcely been investigated in psychiatry. We studied these relations in recurrent depression and matched controls. Results show significant differences and similarities in relations between groups. These may partly explain early development of cardiovascular disease in depression.